Aula de história: uma perspectiva colaborativa na produção de conhecimento no ensino médio - Scarranaro, Márcia Maria (2010)
This research aims to understand critically the activity of teaching and learning of History in a public school of São Paulo state, in Brazil, and its relation to a formation of citizen students. The goal is on the comprehension and critical analysis about the paper of the teachers creating a personal meeting to share the meanings, possibiliting the anticipation of students, and not only the transmission of knowledge without goals. It was realized in a public school, in Mauá city. The students involved was in a third grade, in high school, they study at night. The questions about learning and teaching of History are discussed basing in Bittencourt (1988/1990, 1997/2006), Fonseca (2003, 2004, 2007/2009) e Kuenzer (2004) that points to criticize expositive classes justifying this like a problem that makes the students have a passive position in History classes and in their lives. The learning-teaching process is understood like a social-historic activity culturally situated, focusing a paper of language in the social interaction in the introduction of learning. The theory is based in TASHC- Social Historic cultural Activity theory. According to a Vygotskian theory (1925/2004, 1930/2004, 1930a/1991, 1934/2001), Leontiev (1978) and Engeström (1987, 1999 ,2001). The metodology adopted is a critical collaboration research, according discussed by Magalhães (1994/2007, 1998b/2007, 2003/2007, 2004, 2009p),it is a intervention research focused in the comprehension of context and collaborative production of actions that aims the cohesion of groups, harmonious intimacy and the power of the people that participated of the research. The results reveal that the change in the mediated action, that are in function of needs of perceiving , act and understanding the objective reality, stimulating the exercise of citizen action more participative and critical